The water seeker [compact disc, unabridged] - Holt, Kimberly Willis (Random House/Listening Library, 2010)
Traces the hard life, filled with losses, adversity, and adventure, of Amos, son of a trapper and dowser, from 1833 when his mother dies giving birth to him until 1859, when he himself has grown up and has a son of his own.